A CONCEPTUAL APPROACH TO MANAGING MATERIAL RESOURCES IN PRODUCTION ENTERPRISES - Kokenova A.T.; Syzdykov B.Sh.; Balabekova D.D.; Abylkasym A.B.; Sabenova B.N. (Academic Journal of Physical and Chemical Sciences, 2020)
The applied methods and methods of managing the provision and use of material resources at production enterprises in Kazakhstan are the adaptation of traditional methods for centrally planned economy to the conditions of emerging market relations. The practice of economic activity of industrial enterprises shows their desire to preserve the existing relations with suppliers of material resources in the past. This one-sided orientation leads to the complete dependence of the enterprise on a single partner. The inert policy of enterprises-consumers of material resources encourages suppliers to raise prices above the current level on the world market. In industrial enterprises, the dismantling of centralized material management was not supplemented by the formation of an appropriate mechanism for managing the material intensity of products. As a result, the efficiency of using material resources decreases. The lack of an adequate mechanism for managing processes related to the provision and production use of material resources makes it necessary to study the problem of managing the material resources of production enterprises in the conditions of the formation of market relations. At the same time, the analysis of works that reveal certain aspects of material resource management, rationalization of their use in production enterprises shows that there is no complete concept of management of the enterprise provision and production use of material resources as a single system, the efficiency of which largely depends on the level of costs and the need for working capital. Production enterprises in Kazakhstan need an appropriate methodological basis to form their own model of material resource management, taking into account the specifics of internal potential and the variability of the external environment. In accordance with the intended purpose in the study solved the following tasks: revealed the economic laws of material resources use and the features of their exploitation as an object of management in manufacturing enterprises: based on the selected patterns of use of material resources and synthesis of existing concepts for the management of material resources define the content of management of material resources for the production of the company; reviewed and summarized from the perspective of admissibility for p of industrial enterprises of Kazakhstan; developed by Western experts, methods for managing purchases, deliveries, and inventory of material resources in manufacturing firms; based on system and situational approaches, methodological foundations for managing material resources of an industrial enterprise have been developed.